Associative Reflection of Ethnocultural Concepts in Linguistic Consciousness - Sarekenova Қ.Қ.; Akhmetova М.К. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article examines the structure and content of ethnocultural meanings in the Kazakh language. The purpose of the study is to identify the semantic field of ethnocultural concepts fixed in Kazakh linguistic consciousness, as well as to systematize their attributive, synonymous, and evaluative characteristics. The research objectives included conducting an associative experiment to reveal the respondents’ primary associations with the given words; analyzing the obtained data in terms of frequency and percentage ratios; disclosing the cultural and symbolic meaning of each ethnocultural concept; and determining positive and negative evaluative connotations in linguistic consciousness. The study was conducted in February 2025 with the participation of 150 respondents, during which associations related to 12 ethnocultural concepts were analyzed. As a result, the multifaceted meanings of ethnocultural concepts in the Kazakh language were identified, as well as their connection with national historical memory and spiritual values. Furthermore, the study provided data contributing to a deeper understanding of the ethnocultural system of the Kazakh language and the scientific systematization of the linguistic expression of national culture. The results of this study showed that ethnocultural concepts are firmly preserved in the linguistic consciousness of Kazakh youth, and their symbolic, historical and value significance are still relevant.